2002
DOI: 10.1002/cncr.10370
|View full text |Cite
|
Sign up to set email alerts
|

Postmenopausal cancer risk after self‐reported endometriosis diagnosis in the Iowa Women's Health Study

Abstract: BACKGROUND Endometriosis, the presence of endometrial tissue outside the uterus, has an estimated prevalence between 4% and 10%. A recent study reported that women with a hospital discharge diagnosis of endometriosis were at increased risk of cancer at any site, breast cancer, ovarian cancer, and hematopoietic malignancies, especially non‐Hodgkin lymphoma (NHL). METHODS The authors examined whether self‐reported diagnosis of endometriosis was associated with increased risk of various cancers in the Iowa Women'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
1
14

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(112 citation statements)
references
References 25 publications
6
88
1
14
Order By: Relevance
“…A retrospective case-control study including 1399 patients did not show any association between endometrial cancer and endometriosis [59]. Previously reported data on endometriosis as a risk factor for endometrial cancer are inconclusive [37][38][39][40][41][42]. The studies mentioned have limited case numbers in comparison with the present study, which confirmed an increased risk.…”
Section: Discussionsupporting
confidence: 67%
“…A retrospective case-control study including 1399 patients did not show any association between endometrial cancer and endometriosis [59]. Previously reported data on endometriosis as a risk factor for endometrial cancer are inconclusive [37][38][39][40][41][42]. The studies mentioned have limited case numbers in comparison with the present study, which confirmed an increased risk.…”
Section: Discussionsupporting
confidence: 67%
“…The ectopic lesions often develop as invasive neoplasms and increasing evidence suggests that endometriosis might be a precursor of ovarian epithelial tumors (Brinton et al, 1997;Kobayashi et al, 2007;Melin et al, 2006;Nagle et al, 2008;Olson et al, 2002;Somigliana et al, 2006). Prevention strategies for ovarian cancer, the most lethal gynecologic malignancy, are a research priority, and early identification and treatment of precursor lesions is essential for long-term survival.…”
Section: Introductionmentioning
confidence: 99%
“…It is not clear from the available studies whether endometriosis is associated with an increased risk of breast cancer. [10][11][12][13] An unexpected reduced incidence of cervical cancer was seen in a National Swedish cancer registry study. 14 Alternative explanations to a causal one are an increased number of referrals to gynaecologists for endometriosis and more regular performance of cervical smears.…”
Section: Endometriosis and Other Cancersmentioning
confidence: 98%
“…A definitive link has yet to be made. Similarly, inconclusive, but intriguing, associations have been made between endometriosis and nonHodgkin's lymphoma, 10,11 and melanoma. 11,13 Further work is needed to confirm or refute these findings, particularly as many previous studies included only a small number of subjects.…”
Section: Endometriosis and Other Cancersmentioning
confidence: 99%